Polyhydric SiO2 coating assistant to graft organophosphorus onto glass fabric for simultaneously improving flame retardancy and mechanical properties of epoxy resin composites. (15th August 2022) - Ma, Lili; Liu, Hui; Wen, Xin; Szymańska, Karolina; Mijowska, Ewa; Hao, Chuncheng; Tang, Tao; Lei, Qingquan
Abstract: It is still a great challenge to develop epoxy resin/glass fabric (EP/GF) composites with well-balanced enhancements on flame retardancy and mechanical properties. Herein, a novel strategy that polyhydric SiO2 coating assistant to graft organophosphorus (DOPO) onto GF was developed for simultaneously improving flame retardancy and mechanical properties of EP composites. The grafting amount of DOPO could reach to 43.64 wt% via the helpful bridging of polyhydric SiO2, so that EP composites displayed excellent flame retardancy with the LOI of 37.2%, the V0 rating on UL-94 and a 63.3% decrease on PHRR in cone calorimeter test. According to the analysis of char morphology and structure, the flame retarded mechanism was mainly ascribed to the enhanced barrier effect of a continuous and intergrow char layer, which was composed of GF@SiO2 as framework and P-containing condensed carbon as stuffing. Meanwhile, EP composites exhibited outstanding mechanical performances with 35% and 60% increases on tensile strength and impact strength respectively, which resulted from the special molecular structure of GF@SiO2 - g -DOPO with strong interfacial adhesion with EP chains via hydrogen bond and chemical bond. In summary, this work will be favorable to design multifunctional polymer composites with well-balanced comprehensive performances, and expand their widespread applications in high-end fields. Graphical abstract: Image 1 Highlights: A novel polyhydric SiO2 coating assistant to graft organophosphorus onto GF. The grafting amount of DOPO could reach to 43.64 wt%. Excellent flame retardancy with LOI of 37.2%, V0 rating on UL-94 and a 63.3% decrease on PHRR. Outstanding mechanical performances with 35% and 60% increases on tensile strength and impact strength respectively. The corresponding enhancement mechanisms on flame retardancy and mechanical performances were revealed.